2012
DOI: 10.3329/jom.v13i2.12772
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome Following Dengue Fever in Adult Patient

Abstract: Guillain-Barre syndrome is a post infectious ascending, usually demyelinationg polyradiculoneuropathy. Dengue fever as an antecedent infection in GBS is uncommon. A 39-year-old female presented with acute flaccid weakness of both upper and lower limbs which developed in ascending and progressive fashion following a febrile illness of three days. During work-up IgM for dengue virus was found positive. Diagnosis of Guillain-Barre syndrome was made based on neurologic manifestations, the typical CSF findings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Previous evidence suggests the association between arbovirus infection and GBS [19][20][21][22][23][24][25]. Regarding the frequent and intense dengue, chikungunya, and Zika epidemics, there are few cases described involving neurological complications associated with infection by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggests the association between arbovirus infection and GBS [19][20][21][22][23][24][25]. Regarding the frequent and intense dengue, chikungunya, and Zika epidemics, there are few cases described involving neurological complications associated with infection by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…As the incidence of dengue and DHF is increasing, unusual manifestations are on the rise, although they are being under reported due to the lack of awareness [ 3 ]. Neurological manifestations so far reported include depression, convulsions, encephalopathy, encephalitis, aseptic meningitis, intracranial haemorrhage, intracranial thrombosis, myelitis, mononeuropathies, polyneuropathies, hemifacial spasm, peripheral facial paralysis and Guillain–Barre syndrome (GBS) [ 3 5 ]. GBS or acute inflammatory demyelinating polyradiculopathy (AIDP) is a post infectious ascending, usually demyelinating, polyradiculoneuropathy accompanied by areflexia, motor paralysis, and elevated cerebro spinal fluid (CSF) total protein without pleocytosis [ 5 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Well established associations with GBS are recent infections with Campylobacter jejuni , Cytomegalo virus, Epstein–Barr virus, Mycoplasma pneumonia , HIV. But dengue fever (DF) as an antecedent infection in GBS is uncommon [ 5 , 10 , 11 ]. Several previous reports have described GBS in patients with dengue [ 3 , 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum includes encephalitis, myositis, myelitis, GBS and mononeuropathies 5. GBS or acute inflammatory demyelinating polyradiculopathy is a postinfectious ascending, usually demyelinating, polyradiculoneuropathy 6. Well-established associations with GBS are recent infections with Campylobacter jejuni , cytomegalovirus, Epstein-Barr virus, Mycoplasma pneumonie and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue fever as an antecedent infection in GBS was uncommon a decade back; however, several authors have increasingly described GBS in dengue, majority of these being children and a few cases of postdengue GBS in adults 6 7. It is suggested that the clinical manifestations of GBS in dengue result from an abnormal immune response to non-self antigens which can cross-react with the myelin or axons of peripheral nerves via molecular mimicry 8.…”
Section: Discussionmentioning
confidence: 99%